Regional Anestesia dengan Teknik Thoraco Spinal Anesthesia (TSA): Manfaat dan Tantangan dalam Praktik Anestesiologi - Dwi Lunarta Docterina Sutanti Siahaan (Universitas Methodist Indonesia, 2025)
Thoracic spinal anesthesia (TSA) is a regional anesthesia technique increasingly used in clinical practice as an alternative to general anesthesia, particularly in thoracoabdominal and upper extremity surgeries. This technique offers several benefits, including optimal pain control, hemodynamic stability, and faster recovery. However, the application of TSA also presents challenges, such as the need for specialized skills, the risk of hypotension, and proper patient selection. This article discusses the benefits and challenges of TSA in modern anesthesiology practice and its implications for improving patient clinical outcomes.